Family Planning and Maternal Health: A Study of Jammu District - Kour, Tajinder (National Geographical Journal of India, 2022)
A close interplay exists between the issue of population growth, developmental trends and problems of women's status. It is found that an improvement in women's status through education, employment, access to health services and increase age of marriage had a direct impact on their fertility behaviour. Indian planners have always acknowledged health as an important area for women's development. Access to safe, voluntary family planning is a human right. Family planning is central to gender equality and women's empowerment and a key factor in reducing poverty. In the present paper an attempt has been made to study the family planning and maternal health in Jammu district. The present study is based on both primary and secondary sources of data. The primary data is collected through field survey of 25 wards and 25 villages. The data was collected through interview schedules. The total sample size consists of 300 women respondents.